Parametric study of propulsive forces in front crawl swimming - acceleration effect and flow behavior - Raphaël, G.; Eon, A.; Decatoire, A.; Monnet, T.; Laurent, D.; Samson, M. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The arms play a key role in propulsion (Maglischo, 2003; Takagi et al., 2016). Numerous authors have studied the links between the kinematics of aquatic strokes of the upper limbs and propulsive forces, which are defined as the component of the resultant force in the swimming direction (Berger et al., 1999). The main kinematic parameters in optimising propulsive force have been shown by (Samson et al., 2015). Among these, arm acceleration holds an important place and many authors have studied its role in propulsion (Gardano & Dabnichki, 2006; Kudo et al., 2013; Rouboa et al., 2006; Sanders, 1999). Variations in velocities (accelerations) can generate up to 9 times more force than at constant velocity (Kudo et al., 2013). Although these studies have shown the relevance of acceleration in propulsion, to our knowledge, no parametric study has been carried out to model a relationship between acceleration and propulsive forces. To deepen our understanding of propulsive forces in relation to acceleration, we carried out a parametric experiment under unsteady conditions using a robotic device. The purpose of this paper is to study the role of acceleration on arm propulsion from a basic rotation movement. This work is based on both force and fluid velocity measures, from a robotic arm. Concurrently, a CFD study has been carried out. In so doing, we were able to experimentally observe the evolution of propulsive force versus acceleration (force measurements). Simultaneously, experimental and numerical 2D-PIV fields have enabled us to understand the phenomena (vortex dynamic and flow behaviour around swimmers` arms) behind the generation of these forces.